The Effect of Environmental Cost, Carbon Emission Disclosure, and Sustainability Reporting on Financial Performance of Consumer Non-Primary Sector Companies Listed on the Indonesia Stock Exchange:A Management Accounting Perspective with E-Views Analysis - Rani Nur Az-zahra Osman; Mukhzarudfa Mukhzarudfa; Ratih Kusumastuti; Wiwik Tiswiyanti (PT. Hafasy Dwi Nawasena, 2026)
This study analyzes the effect of environmental cost, carbon emission disclosure, and sustainability reporting on financial performance proxied by Return on Assets (ROA) in consumer non-primary sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The research population includes all consumer non-primary sector companies on the IDX, with a sample of 18 companies selected through purposive sampling technique, yielding 90 observation data (balanced panel). Data analysis employs panel data regression using E-Views 13 software, encompassing Common Effect, Fixed Effect, and Random Effect model estimation selected through the Chow Test, Hausman Test, and Lagrange Multiplier Test. The results indicate that: (1) environmental cost has a significant negative effect on ROA; (2) carbon emission disclosure has a significant positive effect on ROA; and (3) sustainability reporting has a significant positive effect on ROA. Simultaneously, the three independent variables significantly affect financial performance with a coefficient of determination (adjusted R²) of 0.6572 or 65.72%. These findings imply the importance of integrating environmental cost information and sustainability reporting into management accounting systems to support corporate strategic decision-making.